Role of NR1D1 in Bisphenol A-Induced Anxiety-like Behavior and Inflammation in Zebrafish Larvae - Mingjun Wu; Pinyi Chen; Yuting Wang; Xinwei Wang; Yuqianrui Bao; Liqiao Fan; Yuxiao Rao; Xiaoyao Song; Jie Zhang (Toxics, 2025)
Bisphenol A (BPA) is a widespread environmental endocrine disruptor with significant neurodevelopmental and behavioral risks. The present study explored the role of the circadian clock protein NR1D1 in mediating BPA-induced anxiety-like behavior and brain inflammation early in life. Zebrafish embryos exposed to BPA exhibited anxiety-like behavior characterized by altered motor activity patterns. Notably, BPA exposure suppressed the expression of the circadian clock gene nr1d1, accompanied by increased transcriptional and protein levels of pro-inflammatory cytokines, including IL-6, IL-1β, and TNF-α. These changes created a pro-inflammatory microenvironment that disrupted dopamine system homeostasis, contributing to the observed behavioral abnormalities. Activation of NR1D1 using GSK effectively reversed BPA-induced inflammatory responses and restored normal dopamine levels and behavioral phenotypes. These findings highlight NR1D1 as a critical regulator linking circadian rhythm disruption, neuroinflammation, and dopaminergic dysfunction to anxiety-like behavior. This study provides novel insights into the mechanisms underlying BPA-induced neurotoxicity and identifies NR1D1 as a potential therapeutic target for mitigating the adverse effects of early-life BPA exposure.